MicroRNAs regulate TASK‐1 and are linked to myocardial dilatation in atrial fibrillation - Wiedmann, Felix Tobias; Kraft, Manuel; Kallenberger, Stefan M.; Büscher, Antonius; Paasche, Amelie; Blochberger, Pablo L.; Seeger, Timon; Jávorszky, Natasa; Warnecke, Gregor; Arif, Rawa; Kremer, Jamila; Karck, Matthias; et al. (Journal of the American Heart Association, 2022)
Background - - Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia. However, underlying molecular mechanisms are insufficiently understood. Previous studies suggested that microRNA (miRNA) dependent gene regulation plays an important role in the initiation and maintenance of AF. The 2‐pore‐domain potassium channel TASK‐1 (tandem of P domains in a weak inward rectifying K+ channel-related acid sensitive K+ channel 1) is an atrial‐specific ion channel that is upregulated in AF. Inhibition of TASK‐1 current prolongs the atrial action potential duration to similar levels as in patients with sinus rhythm. Here, we hypothesize that miRNAs might be responsible for the regulation of KCNK3 that encodes for TASK‐1. - - Methods and Results - - We selected miRNAs potentially regulating KCNK3 and studied their expression in atrial tissue samples obtained from patients with sinus rhythm, paroxysmal AF, or permanent/chronic AF. MiRNAs differentially expressed in AF were further investigated for their ability to regulate KCNK3 mRNA and TASK‐1 protein expression in human induced pluripotent stem cells, transfected with miRNA mimics or inhibitors. Thereby, we observed that miR‐34a increases TASK‐1 expression and current and further decreases the resting membrane potential of Xenopus laevis oocytes, heterologously expressing hTASK‐1. Finally, we investigated associations between miRNA expression in atrial tissues and clinical parameters of our patient cohort. A cluster containing AF stage, left ventricular end‐diastolic diameter, left ventricular end‐systolic diameter, left atrial diameter, atrial COL1A2 (collagen alpha‐2(I) chain), and TASK‐1 protein level was associated with increased expression of miR‐25, miR‐21, miR‐34a, miR‐23a, miR‐124, miR‐1, and miR‐29b as well as decreased expression of miR‐9 and miR‐485. - - Conclusions - - These results suggest an important pathophysiological involvement of miRNAs in the regulation of atrial expression of the TASK‐1 potassium channel in patients with atrial cardiomyopathy.
Das PDF enthält zusätzlich einen Anhang von 8 Seiten
Gesehen am 25.05.2022